Internal fixation implants for intracapsular hip fractures in older adults - Lewis, SR; Macey, R; Eardley, WGP; Dixon, JR; Cook, J; Griffin, XL (Cochrane Collaboration, 2021)
Background Hip fractures are a major healthcare problem, presenting a huge challenge and burden to patients, healthcare systems and society. The increased proportion of older adults in the world population means that the absolute number of hip fractures is rising rapidly across the globe. The majority of hip fractures are treated surgically. This review evaluates evidence for types of internal fixation implants used in joint‐preserving surgery for intracapsular hip fractures.